(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of migration for many people is economic in nature. Remittance through migration has been serving as a unique instrument to fill the income gap that exists for many rural people. In this context the present study examines the role of remittance send by the urban migrants from the two biggest cities of Nagaland to their home. In the study, it was found that migration for economic reason is increasing in the State in recent times. Though the amount remitted by the migrants was not very large yet it helps the recipient families in various ways leading to the increase in well-being of the migrants’ family in the origin areas. The regression result suggests that variables such as the level of income and educational status of the urban migrants have a significant effect on the remittance they send home.